Investors Behaviour towards Green Marketing (Environmental Friendly) Activities of Firms in Pakistan - Rasheed, Hafsa (British Journal of Marketing Studies, 2013)
This paper aims to find that whether investors' demographics have an impact on their investment preferences? Also whether Pakistani investor's green marketing preferences have an impact on their company related preferences. Factor Analysis, AHP, ANOVA and Regression analysis are applied. The findings suggest that Green marketing practices are becoming one of the most important parts of businesses all over the world. Same is the case with businesses in Pakistan. Like all other practices, green marketing practices also need to incur cost to be performed. Thus companies have to justify these costs with its returns. One of the major groups of stakeholders' is the investors of company, whose primary focus is upon the financial gains and losses of business. In most of the countries, investors are optimistic about green marketing practices and they respond positively for such practices. Results show that investors' investment preferences vary with their varying demographics. Green marketing concerns become more important when they become more educated and when they grow old. It is also found that investors who prefer green concerns not only prefer firm's image and its environmental performance but they also give importance to the financial performance of the company. Pakistani investors are dedicated towards their environment and they prefer to invest in those companies that are environmental friendly.